Association between infection with Helicobacter pylori and risk of gastric cancer: evidence from a prospective investigation. Issue 6788 (1st June 1991) - Forman, D; Newell, D G; Fullerton, F; Yarnell, J W; Stacey, A R; Wald, N; Sitas, F
Abstract : OBJECTIVE–To investigate the association between gastric cancer and prior infection with Helicobacter pylori. DESIGN–Case-control comparison of prevalence of IgG antibodies to H pylori in blood samples collected prospectively, before diagnosis of gastric cancer in the cases. Presence of H pylori antibody (greater than 10 micrograms IgG/ml) determined by enzyme linked immunosorbent assay (ELISA). SUBJECTS–29 men with a subsequent diagnosis of gastric cancer and 116 aged matched controls selected from over 22, 000 middle aged men participating in two ongoing cohort studies (the British United Provident Association study and the Caerphilly collaborative heart disease study), who had provided blood samples during 1975-1982. RESULTS–20 of the 29 cases (69%) and 54 of the 116 controls (47%) were positive for H pylori specific antibody. The median specific IgG concentration was significantly higher in the cases than controls (90 micrograms/ml v 3.6 micrograms/ml, p less than 0.01). The estimated odds ratio for the risk of gastric cancer in those with a history of infection with H pylori was 2.77 (95% confidence interval 1.04 to 7.97, 2p = 0.039). CONCLUSIONS–H pylori infection may be an important cause of gastric cancer; between 35% and 55% of all cases may be associated with such an infection.